2011
DOI: 10.1007/s10995-010-0736-y
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Intake of Folic Acid for the Prevention of Neural Tube Defects Among Lebanese Women of Childbearing Age

Abstract: Since the early 1990s, international recommendations have promoted folic acid supplementation during the periconception period as an effective way of preventing neural tube defects (NTDs). However, the adoption of this recommendation remains insufficient. To assess the awareness and actual intake of folic acid among married Lebanese women aged 18-45 years, a cross-sectional study was conducted among 600 women selected from all five administrative districts in Lebanon, using a multistage cluster sampling proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
3
16
1
Order By: Relevance
“…Beyond folate intake, supplementation of folic acid during the periconceptional period represents one of the best strategies to tackle pregnancy adverse outcomes, as suggested by the WHO in 2006 [17]. However, the prevalence of folic acid supplementation remains often inadequate in several countries [20,68]. Although we showed that only~3% of pregnant women did not take folic acid supplements,~75% of them did not take supplements as recommended (i.e., 4 weeks before conception until 8 weeks after).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Beyond folate intake, supplementation of folic acid during the periconceptional period represents one of the best strategies to tackle pregnancy adverse outcomes, as suggested by the WHO in 2006 [17]. However, the prevalence of folic acid supplementation remains often inadequate in several countries [20,68]. Although we showed that only~3% of pregnant women did not take folic acid supplements,~75% of them did not take supplements as recommended (i.e., 4 weeks before conception until 8 weeks after).…”
Section: Discussionmentioning
confidence: 62%
“…Several studies aimed to identify the main determinants of inadequate supplement use during pregnancy. Among social factors, for instance, it has been demonstrated that younger age [20], low income [71], educational level [68], and employment status [21] might affect the use of folic acid supplements. In our opinion, social inequalities in the use of supplements could be partially explained by the reduced level of knowledge, attitude, and awareness among the more disadvantaged groups [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies in the KSA by Musaiger et al [120,121] and Afshin et al [120,121] revealed that >80% of women aged 18–45 years were unaware of the role played by periconceptional folic acid supplementation. By contrast, in ranges across surveys from the Gulf and Levant region found that 46%–62% of women are aware of the benefits of folic acid and 6%–45% of pregnant women reported taking folic acid supplementation during their first-trimester; the lowest rate of folic acid supplement use was found in Lebanon (6%–14% of women) [122,123,124,125]. In the Feeding Infants and Toddlers Study, Abdulrazzaq et al evaluated the nutrient adequacy of 1000 infants and toddlers in the UAE and found that, although protein and energy intakes approximated the recommended allowance, iron intake was inadequate (<70% of RDA) in 66.8% of infants 6–11 months old and 100% of toddlers 12–23 months old [126].…”
Section: Food Fortification and Dietary Supplementation In The Midmentioning
confidence: 99%
“…Evidence from Lebanon highlights a need for promoting preconception health awareness. In a national survey of married Lebanese women aged 18 to 45 years, Nasr et al found that 40% of the participants had not heard about pre-pregnancy folic acid and its prevention of neural tube defects (NTD) [ 13 ]. Tamim et al showed a low prevalence (14%) of preconception folic acid intake among 5,280 Lebanese pregnant women [ 14 ].…”
Section: Introductionmentioning
confidence: 99%